Stabilisasi Tanah Lempung dengan Metode Kimiawi Menggunakan Garam Dapur (NaCl)(Studi Kasus Tanah Lempung Desa Majenang, Sukodono, Sragen) - Prasetyo, Purnomo Hery, Qunik Wiqoyah, ST., MT, Ir. Renaningsih, MT (2016)
Based on preliminary test results showed the soil in Sukodono, Sragen soil is an inorganic clays of high plasticity, with a value of LL = 85.73%, PL = 24.69%, PI = 61.04%. On the test of soil chemical elements conducted at the Laboratory of Analytical Chemistry MIPA UGM, Sukodono soil contains soil chemical element = 16.86% Al2O3, CaO = 0.92% = 10.81% Fe2O3, MgO = 1.35%, and SiO2 = 63.25%. Based on the value of PI = 61.04% (more than 17%) and the soil need for soil improvement measures. Soil improvement is done by means of chemical soil stabilization using salt (NaCl) with the addition of NaCl percentage of 5%, 10%, 15%, 20% and 25% of the sample weight. Testing was conducted on the test of the physical properties and mechanical properties of original soil and soil mix. The test results and the physical properties original soil water content values obtained mixture, plastic limit, shrinkage limit increases while the density (specific gravity), liquid limit, plasticity index and percent through sieve 200 has decreased. Classification of soil mix NaCl 0% and 5% according to the AASHTO system includes a group of A-7-6 and the mixture NaCl 10%, 15%, 20% and 25% belong to a group of A-7-5. Soil mix NaCl 0%, 5%, 10% and 15% according to the USCS system including CH group and mixtures NaCl 20% and 25% including a group of MH. The test results of mechanical properties of the Standard Proctor test soil mix NaCl 0%, 5%, 10%, 15%, and 20% experienced an increase in volume and a decrease in the weight value optimum moisture content. Maximum volume of heavy grades of 1.45 g / cm3 and the optimum water content as low as 23% on addition of 20% NaCl. CBR has increased the maximum value equal to the state of compaction that results in 20% NaCl percentage. CBR value Unsoaked on NaCl 0% to 9% to 28% NaCl 20% and the CBR Soaked in NaCl 0% by 1% to 3% in 20% NaCl. Maximum development value decreased in 20% NaCl from 0% NaCl development value of 1.51% to 20% NaCl development value of 1.01%.